EVALUATION OF BANK NAGARI'S FINANCIAL HEALTH: RISK-BASED BANK RATING (RBBR) ANALYSIS DURING THE 2020-2023 PERIOD - Hia, Yulia; Komalasari, Sanda Patrisia (Pusat P2M Politeknik Negeri Batam, 2024)
This research aims to evaluate the health level of Bank Nagari using the Risk-Based Bank Rating (RBBR) method during the 2020-2023 period. The RBBR method evaluates bank performance based on four main components: Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital (RGEC). This research uses a quantitative descriptive method by collecting data from the annual financial reports and GCG reports of Bank Nagari for the last four years. This analysis includes measuring various risk indicators such as credit risk, market risk and liquidity risk, as well as evaluating financial performance based on profitability and capital adequacy. The research results show that Bank Nagari's overall health level is very healthy. In 2020, Bank Nagari obtained a composite score of 86%, increasing to 90% in 2021 and returning to stability at 86% in 2022 and 2023. Factors such as Return on Assets (ROA) and Capital Adequacy Ratio (CAR) show consistent improvement, reflecting solid financial performance and good risk management. This research concludes that effective risk management and good GCG practices have contributed to the stability and health of Bank Nagari during the analyzed period.